Characterization And Virulence Studies Of Motile Aeromonads Isolated From Clarias Batrachus And C. Gariepinus And Their Immunization Potential - Sapriyadi, Hambali (1990)
Morphological, physico-chemical, biochemical and virulence characteristics of 30 motile Aeromonas isolates were examined. Selected isolate were investigated for their ability to immunise fish. Four Aeromonas hydrophila, ten Aeromon as hy drop hi la-like and sixte n unspecified Aeromon as spp. we re isolated from C. batrachus and C. gariepinus. These two fish species were collected from fish farms at Bogor, Depok, Sukabumi and Bekasi, West Java. It appears that the virulency of motile aeromonads wa s associated with the type and am ount of extra cellular substances produced.